1988
DOI: 10.1021/jo00240a004
|View full text |Cite
|
Sign up to set email alerts
|

Lewis acid modification of nitric oxide as an oxidizing agent

Abstract: Tertiary amines (CH3)2NR, where R is phenyl or a methyl-substituted phenyl group, in the presence of nitric oxide and a Lewis acid undergo -hydrogen cleavage concurrent with intermolecular hydrogen transfer to yield equal amounts of iminium and ammonium salts in CH2C12 as solvent. When R is a p-or o-methyl-substituted phenyl ring this facile hydrogen transfer reaction also takes place in S02. In CH2C12 no reaction occurs in the absence of the Lewis acid. However, in S02 or in CHC13 with the addition of stoichi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The NSO bond angle of 99° corresponds to a significant out-of-plane distortion of the SO 3 unit and thus further indicates a substantial chemical interaction in the complex. The nitrogen−sulfur distance in the preferred structure is about 0.09 Å longer than the 1.829(5) Å value reported in the solid, indicating that upon crystallization, the N−S bond undergoes a small but significant contraction. Although an effect of this size would be unusual for most covalent bonds, it is reasonable for a dative bond whose formation is incomplete.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The NSO bond angle of 99° corresponds to a significant out-of-plane distortion of the SO 3 unit and thus further indicates a substantial chemical interaction in the complex. The nitrogen−sulfur distance in the preferred structure is about 0.09 Å longer than the 1.829(5) Å value reported in the solid, indicating that upon crystallization, the N−S bond undergoes a small but significant contraction. Although an effect of this size would be unusual for most covalent bonds, it is reasonable for a dative bond whose formation is incomplete.…”
Section: Discussionmentioning
confidence: 59%
“…Although three isotopically substituted species certainly do not provide enough data to fit all parameters, initial attempts were made to determine the structure prior to the observation of the 13 C species. Past work on similar adducts has indicated that it is frequently sufficient to determine only the N−S distance, R(NS), and the NSO angle, α(NSO), while leaving the remaining internal structural parameters of the monomers fixed at their free-molecule values. ,, Because there are slight differences in the pyridine ring structure in the gas phase 26 and in the X-ray structure of the complex, data were fit with the pyridine ring fixed at both its gas-phase structure and its structure in solid py-SO 3 . With either set of pyridine ring parameters, however, the fits were very poor, with residuals of several MHz in all of the B and C rotational constants included.…”
Section: Structure Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…At the temperatures used for the exchange studies there was no evidence for exchange on the nrnr time scale between the SO2 and H2S03 adducts, although it did occur at room temperature. Although the SOz employed in these studies was dried over P2O5 traces of H2SO3 adducts, arising from H20 in SOz, or adsorbed on the glass of the vacuum system, were characterized in other amine systems (15). Chemical shifts of the assignable signals for these adducts are listed in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…As part of our continuing studies on the reactions of Lewis acids with tertiary aromatic amines (15), the reactions of I with SO2 and BF3 are presented here. The crystal structure of 11, a partially hydrolyzed BF3 adduct of I, is also described.…”
Section: General Proceduresmentioning
confidence: 99%